Missing Pathways to Self-Governance: Aboriginal Health Policy in British Columbia - Lavoie, Josée G; Browne, Annette J.; Varcoe, Colleen; Wong, Sabrina; Fridkin, Alycia; Littlejohn, Doreen; Tu, David (International Indigenous Policy Journal, 2015)
This article explores how current policy shifts in British Columbia, Canada highlight an important gap in Canadian self-government discussions to date. The analysis presented draws on insights gained from a larger study that explored the policy contexts influencing the evolving roles of two long-standing urban Aboriginal health centres in British Columbia. We apply a policy framework to analyze current discussions occurring in British Columbia and contrast these with Ontario, Canada and the New Zealand Māori health policy context. Our findings show that New Zealand and Ontario have mechanisms to engage both nation- or tribal-based and urban Indigenous communities in self-government discussions. These mechanisms contrast with the policies influencing discussions in the British Columbian context. We discuss policy implications relevant to other Indigenous policy contexts, jurisdictions, and groups.